The last death of the year [large type] : the new Hercule Poirot mystery - Hannah, Sophie, 1971-; Christie, Agatha, 1890-1976 (Hannah, Sophie, 1971- Hercule Poirot mysteries., 2025)
New Year's Eve, 1932. Hercule Poirot and Inspector Edward Catchpool arrive on the tiny Greek island of Lamperos to celebrate the holiday with what turns out to be a rather odd community of locals living in a dilapidated house. A dark sense of foreboding overshadows the beautiful island getaway when the guests play a New Year's Resolutions game after dinner and one written resolution gleefully threatens to perform 'the last and first death of the year.' Hours later, one of the home's residents is found dead on the terrace.